To find the second term of the sequence, we substitute n=2 into the rule:
A(2) = -9 + (2-1)(3)
A(2) = -9 + 1(3)
A(2) = -9 + 3
A(2) = -6
Therefore, the second term of the sequence is -6.
To find the fourth term, we substitute n=4 into the rule:
A(4) = -9 + (4-1)(3)
A(4) = -9 + 3(3)
A(4) = -9 + 9
A(4) = 0
Therefore, the fourth term of the sequence is 0.
To find the eleventh term, we substitute n=11 into the rule:
A(11) = -9 + (11-1)(3)
A(11) = -9 + 10(3)
A(11) = -9 + 30
A(11) = 21
Therefore, the eleventh term of the sequence is 21.
In conclusion:
Second term: -6
Fourth term: 0
Eleventh term: 21
Find the second, fourth, and eleventh terms of the sequence described by each rule
A(n)=-9+(n-1)(3)
Second:__
fourth:__
eleventh:__
1 answer